Construção de sentidos a partir do debate sobre desconstrução de estereótipos de gênero em aulas de língua inglesa: rizomatizações e reterritorializações - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
The aim of this research was to investigate how students inserted in the scenario of Vocational Education make meaning from the debate of deconstruction of gender stereotypes emerging in English classes. From the perspective of a research(ERICKSON, 1986) and having MultipleLiteracies Theory – MLT, Multiliteracies and Critical Literacies (COPE;KALANTZIS, 2000; KALANTZIS; COPE, 2012; MASNY, 2010; MASNY & COLE, 2009; MASNY & WATERHOUSE, 2011; MONTE MÓR, 2008, 2012, 2013; MENEZES DE SOUZA, 2011;WATERHOUSE, 2011) as our theoretical framework, the present study was carried out during a school bimester back in 2017 and involved freshmen students of the technical integrated courses (Buildings, Chemistry, Computing) of the Federal Institute of Education, Science and of Goiás – IFG. Research material derived from the study was problematized through the lens of rhizoanalysis (DELEUZE, amp;GUATTARI, 1980;MASNY, 2010; MASNY & COLE, 2009; MASNY & WATERHOUSE, 2011; WATERHOUSE, 2011). Through this study we concluded that in the Vocational Education scenario, whose aim is students’ omnilateral formation, English classes may be considered as a space for critical knowledge production, according to what proposes critical/multiple literacies, once language is regarded as social praxis, as stated in BNCC.
Meaning making stemming from the deconstruction of gender steretypes debate in english classes : rhizomatizations and reterritorializations
Keywords: Construção de sentidos; Educação Profissional e Tecnológica; Língua Inglesa; Teoria dos Letramentos Múltiplos; Desconstrução de estereótipos de gênero; Meaning making; Vocational Education.; English language; Multiple Literacies Theory – MLT; Deconstruction of gender stereotypes; CIENCIAS HUMANAS::EDUCACAO